"Getting by": People with learning disability and the financial responsibility of independent living. (7th May 2020) - Conder, Jennifer Ann; Mirfin‐Veitch, Brigit Frances
Accessible summary: People with learning disability who are living independently can find it hard to live well on their limited income. We interviewed 20 adults with learning disability who were living independently. They told us that living independently meant that they had choices. They also told us that it was difficult to afford things like going to dentists and doctors or going on holiday. Some liked to manage their own money while others liked having other people help them manage their money. Governments need to make sure people with learning disability are getting the support they need. Abstract: Background: Within Aotearoa New Zealand (ANZ), disability policy is directed at increasing choices for disabled people. However, funding to individuals remains insufficient to address wider social inequities that exist. While people with learning disability enjoy the freedom of living independently, they can be at risk of poor health outcomes and limited opportunities to fully engage within their community. Method: This qualitative research explored the experience of living independently with 20 adults with learning disability within ANZ. Taking a constructivist perspective, interview transcripts were analysed to develop an understanding of their experience. Multiple readings resulted in comparison and contrast of data. The researchers discussed developing themes before settling on final themes. Results: With regard to money management, two themes were identified. The first illustrates the challenges of managing a budget, while the second highlights what people's limited budgets meant in terms of how they were able to live. Conclusion: This research reinforced previous studies whereby people with learning disability place a high value on having choices. However, it also demonstrated that social inequities within ANZ are not being addressed, as without other financial support, people on a benefit struggled to afford medical and dental care, or holidays and other leisure activities.